Efficacy of rimegepant for the acute treatment of migraine based on triptan treatment experience: Pooled results from three phase 3 randomized clinical trials. (February 2023) - Lipton, Richard B; Blumenfeld, Andrew; Jensen, Christopher M; Croop, Robert; Thiry, Alexandra; L'Italien, Gilbert; Morris, Beth A; Coric, Vladimir; Goadsby, Peter J
Background: This post-hoc analysis from three phase 3 treatment trials of rimegepant 75 mg — an oral small molecule calcitonin gene-related peptide receptor antagonist for acute and preventive treatment of migraine — assessed efficacy in adults with migraine based on triptan treatment experience. Methods: Participants were assigned to one of four groups based on triptan treatment experience: insufficient response (e.g. lack of efficacy and/or poor tolerability) to 1 triptan, insufficient response to ≥2 triptans, current triptan users, and triptan-naïve participants. The co-primary efficacy endpoints were pain freedom and most bothersome symptom freedom at two hours postdose. Results: In the three trials (N = 3507; rimegepant n = 1749, placebo n = 1758), 1235 (35.2%) participants had a history of insufficient response to 1 triptan (n = 910 [25.9%]) or ≥2 triptans (n = 325 [9.3%]), and 2272 (64.8%) had no history of insufficient response to triptans (current use = 595 [17.0%], naïve = 1677 [47.8%]). Rimegepant was effective on the co-primary endpoints in all subgroups ( p  ≤ 0.013), except for freedom from the most bothersome symptom in the triptan-naïve group ( p  = 0.06). No differences on co-primary endpoints were found in pairwise comparisons of rimegepant-treated participants. Conclusions: Rimegepant was effective for the acute treatment of migraine in adults with a history of insufficient response to 1 or ≥2 triptans and in current triptan users. Efficacy on co-primary endpoints did not differ based on the number of insufficient triptan responses. Trial registration: Clinicaltrials.gov: NCT03235479, NCT03237845, NCT03461757